2013
DOI: 10.5194/hess-17-4471-2013
|View full text |Cite
|
Sign up to set email alerts
|

Responses of natural runoff to recent climatic variations in the Yellow River basin, China

Abstract: Abstract. The zero-flow phenomenon appeared frequently in the lower reaches of the Yellow River in China in the 1990s, whereas it has almost disappeared in recent years. The disappearance of the zero-flow phenomenon should be mainly attributed to the recent water management practices. However, little is known about the effects of recent climatic variations on natural runoff. In this study, we investigated the impacts of climatic variations on natural runoff above the Huayuankou station. The results indicate th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
55
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(63 citation statements)
references
References 51 publications
7
55
1
Order By: Relevance
“…Precipitation may directly impact the conditions of runoff yield or may affect the water supple conditions of evaporation and further affect runoff. Previous studies reported that precipitation decrease was the dominant factor of declining runoff in the Futuo River catchment and the Yellow River basin (Tang et al, 2013), agreeing with our results.…”
Section: Effect Of Climate Change On Runoffsupporting
confidence: 93%
“…Precipitation may directly impact the conditions of runoff yield or may affect the water supple conditions of evaporation and further affect runoff. Previous studies reported that precipitation decrease was the dominant factor of declining runoff in the Futuo River catchment and the Yellow River basin (Tang et al, 2013), agreeing with our results.…”
Section: Effect Of Climate Change On Runoffsupporting
confidence: 93%
“…Results of the original climate elasticity method. 1958Turc (1954Pike (1964) Table 3. Results of the improved climate elasticity method.…”
Section: Discussionmentioning
confidence: 99%
“…Climate change is expected to extensively alter global hydrological cycles (Legesse et al, 2003;Milly et al, 2005;Piao et al, 2007;Tang et al, 2013) by primarily changing the pattern of precipitation (IPCC, 2013;Sun et al, 2012). After the falling of precipitation into basins, human activities including land use change, dam construction, river diversion, and other engineering and management practices also modify hydrological cycles locally and therefore temporal and spatial distribution of water resources (Govinda, 1995;Milly et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…For the Yellow Sea and South China Sea, a 7-16% increase in annual precipitation and runoff is projected for this period (Table 2.3). Our modeling results are generally in agreement with existing studies (Milliman & Ren 1995;Tang et al 2013;Yan-Chun 1998), indicating that the basins of the Bohai Gulf are located in drier areas than the basins of the other seas. The annual precipitation is in the range of 300 to 700 mm per year for the Yellow basin , which is in agreement with our results.…”
supporting
confidence: 91%
“…The annual precipitation is in the range of 300 to 700 mm per year for the Yellow basin , which is in agreement with our results. Several studies (Fu et al 2004;Tang et al 2013;Wang et al 2007;Wang et al 2013b;Yan-Chun 1998) indicate a large spatial and temporal variation in runoff and precipitation in the large river basins (e.g., Yellow, Yangtze) from the 1960s to the 1990s. For example, YanChun (1998) showed a slight increase in annual runoff for the Yellow from 1970 to 1989 and a decrease after the 1990s.…”
mentioning
confidence: 99%